China-EU relations in a new era of global transformation - Li, Xing <<[HerausgeberIn]>> (Routledge, Taylor & Francis Group, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- List of illustrations -- List of tables -- List of contributors -- 1 China-EU relations at a crossroads: "systemic rivalry" or "strategic partnership"? -- 2 Europe-China and the Third Way: steering order in times of change. Evidence from the AIIB and WTO reform -- 3 Not getting its act together? The European Union's policy towards China -- 4 China and the EU: convergence through multilateralism -- 5 The Russian energy and climate nexus and the Sino-Russian relationship -- 6 The EU's struggle of "standing in two boats": the dual complexity of the Belt and Road in China-EU relations -- 7 One belt, multiple roads: Moscow and Rome in China's geo-economic calculations -- 8 The ideational impact of China's Belt and Road in Europe: cooperation and competition as pathways of principle-diffusion -- 9 The evolving role of the EU in intensifying great power politics in the Arctic - potential implications for EU-China relations -- 10 European-Russian-Chinese Arctic energy system -- 11 China and Central and Eastern Europe: the case of the Baltic states -- 12 EU and China's strategic partnership on the Blue Economy: challenges and opportunities -- 13 China-EU economic relations: where to go? Implications from a longitudinal case study of international acquisition -- 14 The role of culture in order-building: lessons from China's engagement on the borders of the EU -- 15 Framing Chinese tourism in Europe: golden geese or gaggles? -- Index.
Description based on publisher supplied metadata and other sources.